(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The transition of our country’s economy to market relations demands an improvement in the quality of agricultural products and elevating them to a level where they can compete in the global market. In this regard, an important task for the workers of the sericulture sector is to prepare high-quality silkworms that meet world standards. To achieve this, it is necessary to strictly follow the sericulture agrotechnics to obtain silkworms with clean cocoons that are well-formed, long, slender, and free from defects. Unfortunately, it is known that a significant number of defective silkworms are present even in purebred silkworm groups and are delivered to silkworm reception points.